2017
DOI: 10.1016/j.sna.2016.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Multi-mode strain and curvature sensors for soft robotic applications

Abstract: In this paper we describe the fabrication and testing of elastomer-based sensors capable of measuring both uniaxial strain and curvature. These sensors were fabricated from Sylgard 184, which is a transparent silicone elastomer. We created microchannels directly in silicone elastomer substrates using a laser to ablate material. The sensing element was an alloy of gallium and indium, which is liquid at room temperature, contained within the laser-created microchannels. As the substrate deformed, the microchanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 33 publications
0
62
0
3
Order By: Relevance
“…By embedding a pair of displacement sensors into the SPA, we are able to determine distinctly both extension and bending by calculating the mean and difference of the two sensor measurements, respectively. This approach is similar to that reported by [24], wherein the sum and difference of the values reported from two curvature/strain sensors mounted back-to-back were used to report linear strain and curvature. Using the sSPAs presented here, the extension and bending angle can be determined from two sensor values and the pneumatic pressure applied to the actuators.…”
Section: Introductionmentioning
confidence: 87%
“…By embedding a pair of displacement sensors into the SPA, we are able to determine distinctly both extension and bending by calculating the mean and difference of the two sensor measurements, respectively. This approach is similar to that reported by [24], wherein the sum and difference of the values reported from two curvature/strain sensors mounted back-to-back were used to report linear strain and curvature. Using the sSPAs presented here, the extension and bending angle can be determined from two sensor values and the pneumatic pressure applied to the actuators.…”
Section: Introductionmentioning
confidence: 87%
“…The accuracy of the sensor could be increased with a larger number of channels, but at the cost of spatial complexity. Edward et al [31] presented their work on a multimode strain and curvature sensors, as shown in Figure 10c. Sensor molds were 3D-printed and the encasing material was Ecoflex since this is one of the most popular encasing materials for making soft and stretchable sensors.…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…[161] All phenomena with regard to the origin of color arises from the interaction between electromagnetic waves of light and vibration of electrons in the medium where light passes through. [31] Copyright 2017, Elsevier. On the other hand, when the material has a periodic distribution of refractive index, which is Adv.…”
Section: Optical Sensors With Organic Materialsmentioning
confidence: 99%
See 2 more Smart Citations